First Report of Spinal Anesthesia for Cesarean Delivery in a Parturient With Jeune Syndrome: A Case Report. Issue 2 (February 2021) - Kondo, Hiroaki; Hyuga, Shunsuke; Fujita, Tomoe; Adachi, Mariko; Mochizuki, Junko; Okutomi, Toshiyuki
Abstract : Jeune syndrome, also known as asphyxiating thoracic dystrophy, is a rare form of autosomal recessive skeletal dysplasia. Respiratory distress due to thoracic and lung dysplasia is the primary complication associated with this disorder in neonates. Women with Jeune syndrome seldom conceive and give birth, as only a few survive until adulthood. Herein, we report the world's first case of a cesarean delivery under spinal anesthesia in a pregnant woman with Jeune syndrome with a history of chest wall reconstruction and spinal fusion surgeries.